Examining Faculty Perception of Their Readiness to Teach Online - Florence Martin; Kiran Budhrani; Chuang Wang (Online Learning, 2019)
Faculty readiness to teach online is a state of faculty preparedness for online teaching. In this study, it is measured by faculty attitudes on the importance of online teaching competencies and their ability towards online teaching. Validity and reliability of faculty responses to an online instrument and factors related to faculty perception are examined. Descriptive statistics and item level means for the competencies are provided. For course design, course communication and technical, the faculty rated the perception of importance higher than their ability whereas for time management their perception of ability was rated higher than their attitude on importance. MANOVA showed significant differences in gender, years of teaching online, and delivery method for faculty perceptions of importance of online teaching competencies. Significant differences were also noted in years of teaching online and delivery method with respect to ability to teach online.